A case report of patient with severe acute cholangitis with tigecycline treatment causing coagulopathy and hypofibrinogenemia. Issue 49 (December 2017) - Wu, Xiaoqin; Zhao, Ping; Dong, Liang; Zhang, Xiuhong
Abstract: Rationale: Tigecycline is the first member of the glycylcycline family. There are rarely reports of tigecycline causing coagulopathy and hypofibrinogenemia until now. We report a case on tigecycline-associated coagulopathy and hypofibrinogenemia and discuss the characteristics of the adverse reaction. Patient concerns: A 47-year-old male patient with severe acute cholangitis who developed sepsis was treated with a high dosage (100 mg twice daily) of tigecycline. He experienced coagulopathy and hypofibrinogenemia as substantiated by increased levels of prolonged prothrombin time (PT), the international normalized ratio (INR) and activated partial thromboplastin time (APTT), and in particular, the fibrinogen (FIB) levels obviously decreased. Diagnoses: Coagulopathy and hypofibrinogenemia. Interventions: We discontinued tigecycline and gave the patient several blood products to prevent spontaneous bleeding. Outcomes: The adverse reaction disappeared after the withdrawal of tigecycline. After 30 days of hospitalization, the patient discharged with symptom free. Lessons: We suggest that coagulation parameters should be closely monitored in patients treated with tigecycline, specifically in patients who may be renal insufficiency, female or use the high-dose.